Effects of Workplace Parent Management Training on Marital and Job Satisfaction among Iranian Working Parents - Mousavi, Masoumeh; Alavinezhad, Ramin; Moosavi, Arezoo (Frontiers in Sociology, 2017)
Abstract Background: Shifting the focus of PMT to parents and discussing implications for maximizing the outcomes of PMT for the entire family is new and promising. Objective: We aimed to examine the efficacy of work place parent management training (PMT) on job and marital satisfaction among staff members of an academic center. Methods: We held eight PMT sessions (1.5 hour each) for 20 staff members who were parents to children in the age range of 2 to 12 years. Dyadic Adjustment Scale (DAS) and Occupational Descriptive Index (HSE) were used for baseline and post-intervention data gathering. DAS higher scores indicate higher marital adjustment satisfaction and higher HSE scores indicate higher occupational stress. To analyze changes in HSE and DAS scores over time paired t-test and Wilcoxon Signed Rank test were used respectively. Results: All DAS sub-scales increased from baseline to the final session except for affectional expression which was not significant. We found no significant changes in total or sub-scale HSE scores among participants. Conclusion: Findings of the present study underscore the role of psycho-education usage in work environment and provide evidence about the importance of designing interventions concerning working parents. Implications of parent management training are discussed in the text.